Investigations on Tensile and Flexural Characteristics of Fly Ash and Banana Fiber-Reinforced Epoxy Matrix Composites - GOPALAN, Venkatachalam; SHARMA, Shashank Kumar; JANGID, Anil Kumar; PRAGASAM, Vignesh; SATONKAR, Nilesh; CHINNAIYAN, Pandivelan (Engineering Transactions, 2020)
Polymer matrix composites (PMCs) generally use the inorganic and non-biodegradable materials as reinforcements. This paper presents a PMC with reinforcement of fly ash and banana fiber. The epoxy resin is used as a matrix. This paper investigates the influences of the percentage of fly ash, the percentage of banana fiber and the size of banana fiber on tensile and flexural behaviors of fly ash and banana fiber reinforced epoxy matrix composite. Taguchi’s orthogonal array is used in the design of the experiments in the sample preparations. Analysis of variance (ANOVA) is employed to find the significance of input parameters on tensile and flexural behaviors.